Comparación de la cicatrización clínica alveolar post exodoncia simple con y sin sutura - Huamaní Muñoz, Balbín Wilder (2008)
The purpose of the present research was to compare the characteristics the process of alveolar clinical healing post simple exodontia with and without suture. The research was a simple randomized clinico test and was made in the Hospital of Support I Albrecht — Trujillo of EsSalud, during the months of January to April of the 2008, with a sample of study of thirty insured patients between twenty to fifty years old of bot h sexes. The characteristics of the alveolar healing of hemostasia, inflamation, weave of granulation, epithelization and detritus presence in the tooth socket were compared clinically. In all there was statistical difference; thus, very good hemostasia in the sutured tooths sockets was 867% and in tooths sockets without suture 3,3 Oh; the slight inflammation to the third day in the tooths sockest with suture was 100% and in the tooths sockets without suture 66.7%; the complete weave of granulation to the fourteenth day in the tooths sockets with suture was 63,3% and in the tooths sockes without suture 16.7%; the complete epithelization to the twenty eighth day in hte tooths sockest with suture was 100% and in the tooths sockets without suture 67.7% ; and the presence of detritus to the twenty-four hours in the tooths sockets with suture was 10% and in the tooths sockes without suture 36.7% . These results improve hemostasia they disminish the pain, the inflamation and the detritus presence, and improve the times of granulation and of epitelizacion, when wi th suture tooths socket.